UV and Gamma-Ray Space Telescope Systems 2004
DOI: 10.1117/12.556838
|View full text |Cite
|
Sign up to set email alerts
|

Astronomical soft x-ray mirrors reflectivity enhancement by multilayer coatings with carbon overcoating

Abstract: A number of X-ray astronomical missions of near future will make use of hard X-ray optics with broad-band multilayer coatings. However multilayer mirrors can be also useful to enhance the effective area of a given X-ray telescope in the "classical" low energy X-ray band (0.1 -10 keV), the window where X-ray spectroscopy provides very useful plasma diagnostics) with a consistent gain with respect to usual single-layer reflectors. Multilayers for soft X-rays are based on stacks with constant d-spacing (in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…A substrate and rib thickness of 150 μm and wafer thickness of 750 μm enables a pore structure of 0.6 × 1.5 mm with ∼70% aperture efficiency, which results in a low energy collecting area of ∼70 cm 2 for an XOU. An overcoat of carbon on the iridium-coated reflecting surfaces of HPOs can provide enhanced low energy reflectivity [15].…”
Section: X-ray Opticsmentioning
confidence: 99%
See 1 more Smart Citation
“…A substrate and rib thickness of 150 μm and wafer thickness of 750 μm enables a pore structure of 0.6 × 1.5 mm with ∼70% aperture efficiency, which results in a low energy collecting area of ∼70 cm 2 for an XOU. An overcoat of carbon on the iridium-coated reflecting surfaces of HPOs can provide enhanced low energy reflectivity [15].…”
Section: X-ray Opticsmentioning
confidence: 99%
“…An inner annular radius of 0.67 m, limited by the MSC launch adapter, accommodates HPOs with small grazing angles such that the collecting area at 10 keV is ∼0.8 m 2 . If multi-layer coatings are used on the inner HPO the high energy response can be extended to give ∼0.1 m 2 at 30 keV [15]. An outer aperture radius of 2.1 m can be accommodated within the launcher fairing including a baffle skirt of width ∼16 cm.…”
Section: X-ray Opticsmentioning
confidence: 99%
“…Pareschi et al 17 have recently shown that a thin Coating of Carbon, overimposed to the gold coating, can fill this gap and increase the effective area in the 2 -3 keV band. 17,18 This possibility will be seriously considered.…”
Section: Opticsmentioning
confidence: 99%
“…Subsequently, Pareschi et al [4] pointed out that the deliberate employment of a low density external film over any mirror acts to reduce the photoelectric absorption when the mirror is in the total external reflection regime. In such a case the effective area of the mirror could intentionally be increased between 1 and 4 keV.…”
Section: Introductionmentioning
confidence: 99%